Effects of Lutein on Hyperosmoticity-Induced Upregulation of IL-6 in Cultured Corneal Epithelial Cells and Its Relevant Signal Pathways. (7th March 2016) - Chao, Shih-Chun; Nien, Chan-Wei; Iacob, Codrin; Hu, Dan-Ning; Huang, Sheng-Chieh; Lin, Hung-Yu
Abstract : Dry eye is a common disorder characterized by deficiency of tear. Hyperosmoticity of tear stimulates inflammation and damage of ocular surface tissues and plays an essential role in the pathogenesis of dry eye. Cultured human corneal epithelial (CE) cells were used for the study of effects of lutein and hyperosmoticity on the secretion of IL-6 by CE cells. Cell viability of CE cells was not affected by lutein at 1–10  μ M as determined by MTT assay. Hyperosmoticity significantly elevated the secretion of IL-6 by CE cells as measured by ELISA analysis. The constitutive secretion of IL-6 was not affected by lutein. Lutein significantly and dose-dependently inhibited hyperosmoticity-induced secretion of IL-6. Phosphorylated- (p)- p38 MAPK, p-JNK levels in cell lysates and NF- κ B levels in cell nuclear extracts were increased by being exposed to hyperosmotic medium. JNK, p38, and NF- κ B inhibitors decreased hyperosmoticity-induced secretion of IL-6. Lutein significantly inhibited hyperosmoticity-induced elevation of NF- κ B, p38, and p-JNK levels. We demonstrated that lutein inhibited hyperosmoticity-induced secretion of IL-6 in CE cells through the deactivation of p38, JNK, and NF- κ B pathways. Lutein may be a promising agent to be explored for the treatment of dry eye.